Mechanisms of isoniazid and rifampicin-induced liver injury and the effects of natural medicinal ingredients: A review - Xiuping Zhuang; Xiuping Zhuang; Li Li; Tianyi Liu; Rui Zhang; Peimin Yang; Xin Wang; Long Dai (Frontiers Media S.A., 2022)
Isoniazid (INH) and rifampicin (RFP) are the first-line medications for tuberculosis treatment, and liver injury is the major adverse effect. Natural medicinal ingredients provide distinct benefits in alleviating patients' symptoms, lowering the liver injury risk, delaying disease progression, and strengthening the body's ability to heal. This paper summarises the recent research on the mechanisms of INH and RFP-induced liver injury and the effects of natural medicinal ingredients. It is believed that INH-induced liver injury may be attributed to oxidative stress, mitochondrial dysfunction, drug metabolic enzymes, protoporphyrin IX accumulation, endoplasmic reticulum stress, bile transport imbalance, and immune response. RFP-induced liver injury is mainly related to cholestasis, endoplasmic reticulum stress, and liver lipid accumulation. However, the combined effect of INH and RFP on liver injury risk is still uncertain. RFP can increase INH-induced hepatotoxicity by regulating the expression of drug-metabolizing enzymes and transporters. In contrast, INH can antagonize RFP-induced liver injury by reducing the total bilirubin level in the blood. Sagittaria sagittifolia polysaccharide, quercetin, gallic acid, and other natural medicinal ingredients play protective roles on INH and RFP-induced liver injury by enhancing the body's antioxidant capacity, regulating metabolism, inhibiting cell apoptosis, and reducing the inflammatory response. There are still many gaps in the literature on INH and RFP-induced liver injury mechanisms and the effects of natural medicinal ingredients. Thus, further research should be carried out from the perspectives of liver injury phenotype, injury markers, in vitro and in vivo liver injury model construction, and liver-gut axis. This paper comprehensively reviewed the literature on mechanisms involved in INH and RFP-induced liver injury and the status of developing new drugs against INH and RFP-induced liver injury. In addition, this review also highlighted the uses and advantages of natural medicinal ingredients in treating drug-induced liver injury.